Aktivitas Teman Cerita Dan Mading Sebagai Sarana Ekspresi Emosi Dan Kreativitas Pada Pasien Skizofrenia RSKD Dadi Provinsi Sulsel - Novi Yanti Pratiwi; Andi Nur Wulandari; Firdhana Atshila Ibrahim; Nurul Fikria; Qhanita ghanaya Has; Yenilia Rezky Pramudyanti (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
People with mental health problems often receive a bad stigma in the eyes of people. People with mental disorders (ODGJ) are often ostracized and exiled from their surroundings because they are often considered to be disruptive. The first form of psychological aid for mental health disorders is to look, listen and relate. This activity carries out storytelling and madding activities as a means of expressing feelings and creativity. The aim of this activity is as a form of first psychological aid by providing space for patients at RSKD Dadi, South Sulawesi Province to talk about their feelings or activities, so that patients continue to receive social support. This activity was carried out in 3 sessions. Each session takes 1 hour per session. There are 4 participants in this activity with a diagnosis of schizophrenia. This activity will be carried out on November 8, 2023, November 9, 2023, and November 10, 2023. This activity also uses media to channel patient creativity. The results of the "Story Friend" program were patients who initially had difficulty telling stories and closed themselves off. After the "Story Friend" program, the patient began to tell how he was, what he felt and the things he liked. Patients appear to be starting to open up and are actively involved in creatively preparing wall materials.